Analysis Of Price Perception, Brand Awareness, Delivery Quality On Customer Satisfaction And Repurchase Intention: Case Study On Consumers Of Menantea Products In Pajajaran, Bogor - Dhimas Mahardhika; Adi Nurmahdi (Dinasti Publisher, 2023)
This research was conducted to know the effect of perceived price, brand awareness, quality of delivery on customer satisfaction and repurchase intention. This study used Menantea products in Pajajaran, Bogor and the number of samples used in this study were 255 respondents. This study used a purposive sampling, a questionnaire procedure, and used partial least squares (PLS). The findings explained that perceived price, brand awareness, and quality of delivery had a significant impact on customer satisfaction and repurchase intention. Customer satisfaction has a positive and significant effect on repurchase intention. The management implication in this study is to increase repurchase intention and customer satisfaction. It is necessary to improve product quality so that consumers have the impression that the prices offered are in accordance with quality, increase consumer awareness via internet promotions, and improve the quality of product/service delivery by increasing operating hours, to serve consumers.